Iodate reduction by marine aerobic bacteria - Kine, Ken; Yamamura, Shigeki; Amachi, Seigo (Frontiers in Microbiology, 2024)
Iodate reductase (idr) gene cluster (idrABP1P2) is involved in bacterial iodate (IO3 -) respiration under anaerobic conditions. Putative idr gene clusters are present in both anaerobic and aerobic bacteria; however, the specific physiological roles of idr genes in aerobic bacteria remain unclear. Therefore, in this study, three marine aerobic bacteria with putative idr gene clusters (Roseovarius azorensis, Notoacmeibacter marinus, and Aliiroseovarius sediminilitoris) were grown in the presence of iodate to determine whether they can reduce iodate to iodide (I -). All tested bacteria almost completely reduced 2 mM iodate under static conditions but only reduced 0.1-0.5 mM iodate under shaking conditions. Moreover, the washed cell suspension of R. azorensis reduced iodate only when the cells were pre-grown statically in the presence of iodate. Transcriptional analysis revealed that the expression levels of idrA, idrB, idrP1, and idrP2 genes were upregulated in R. azorensis when the cells were grown statically in the presence of iodate. Specifically, idrA expression was induced by 0.1 µM iodate and was up to 14-fold higher compared to that of the non-iodate control. These results suggest that marine aerobic bacteria reduce iodate under oxygen-limited conditions, and that this capacity is induced by environmentally relevant levels of iodate in seawater. Our results suggest that marine aerobic bacteria contribute to iodide production in marine surface waters, thereby affecting the global iodine cycling and ozone budget.